Adoption of soil conservation practices by mandarin (Citrus reticulata B.) farmers in Gulmi, Nepal - Kisan Khang; Manish Yadav; Mukesh Kumar Jha (Innovations in Agriculture)
Mandarin has a tremendous potential for export and increased income for farmers of Nepal. However, in the recent years, soil degradation and erosion are the major challenges faced by the citrus enterprises especially in the hilly region of Nepal. The declining status of production and productivity cannot be checked without the transfer of site-specific and commodity-based knowledge and skills to the corresponding farmers. A study was carried out in 2023 to examine the soil conservation practices and status of technology adoption among the mandarin farmers. A total of 80 households from three wards of Dhurkot rural municipality of Gulmi district were selected on purpose for the study. Data were collected through interviews, key informant interviews, and focus group discussion, using semi-structured questionnaire, then the descriptive analysis was done using MS Excel and SPSS (Version 23.0). The results revealed that mainly three types of soil were presented in the study areas viz. luvisols, cambisols and sandy gravel, which are highly prone to soil erosion. The average area under mandarin cultivation was reported to be 0.74 hectare, with an estimated productivity of 7.6 metric tons per hectare. Approximately 95% of the respondents were familiar with soil degradation and its consequences in mandarin production. Accordingly, 96.2% of the respondents had adopted some forms of soil conservation practices like sod culture (40%), minimum tillage (36.2%), liming (40%), terracing and cover cropping (95%) and integrated plant nutrient system (31.2%), alongside the traditional stone bunds and mulching. The findings suggested that an increased participation in trainings and contact with extension agents has a significant influence on the importance of capacity building of the farmers regarding sustainable soil conservation technology, innovative cultivation practices, and ensuring frequent extension services to the farmers. Implementing these measures is expected to enable mandarin farmers in Nepal to check annual losses of soil fertility due to soil erosion and landslides, thereby contributing to commercialization of citrus.